Banking: Past and present - Ismail Özsoy; Salavat Sayfullin (IBSU Scientific Journal (IBSUSJ), 2006)
The paper presents the evolution of the banking through out history to modern days. The roots of banking reviewed and the changes are expressed. Reasons for bank evolution is presented and first banking operations are described. The difference between past and present is traced out.
Keywords: 330; Banking; ancient banking; modern banking; deposits; loan